2019
DOI: 10.14218/jcth.2019.00052
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Characteristics and Treatment Patterns of the Patients Recruited to the China Registry of Hepatitis B

Abstract: Background and Aims: Chronic hepatitis B virus (HBV) infection remains a major public health problem globally. Here, we describe the baseline characteristics and treatment profiles of HBV-infected patients recruited to the China Registry of Hepatitis B. Methods: Inclusion criteria were patients with different stages of chronic HBV infection and complete key data. Exclusion criteria were patients with hepatocellular carcinoma. The baseline clinical, laboratory and treatment profiles were analyzed. Results: Fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Previous studies showed that the distribution of different immune states in different age groups was different 23 . The proportion of HBeAg‐negative phenotypes presented an increasing trend with the increase of age, while the proportion of HBeAg‐positive phenotypes showed a decreasing trend 24 .…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies showed that the distribution of different immune states in different age groups was different 23 . The proportion of HBeAg‐negative phenotypes presented an increasing trend with the increase of age, while the proportion of HBeAg‐positive phenotypes showed a decreasing trend 24 .…”
Section: Discussionmentioning
confidence: 94%
“…Age is a vital factor affecting the natural course and long term outcomes of patients with chronic HBV infection, and the incidence of adverse events increase with age [26,27] . In addition, the HBeAg-positive phase of CHB is usually associated with viral repli cation and hepatitis activity [28,29] .Persistent presence of HBeAg has been demonstrated to be associated with a higher risk of brosis progression and cirrhosis development.Therefore, it is important for clinicians to monitoring disease progression in GZ CHB patients with older age and high-normal ALT who might have higher risk of advanced disease There were several limitations that affected the interpretation of our ndings. This study was a retrospective crosssectional study that could not exclude selection bias of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Data from Beijing indicated that coverage of antiviral therapy by basic medical insurance since 2011 has reduced the risk of developing liver-related death for patients with CHB (8). The selection of a potent NA with high barrier to resistance as a first-line therapy, especially in areas with limited healthcare resources, may provide the best chance of achieving treatment goals (41). Until 3 years earlier, NA with high barrier to resistance like ETV and TDF had been much more expensive, so they were not widely used.…”
Section: Reimbursement Policy and Massive Price Reductions For Antiviralsmentioning
confidence: 99%
“…In 2019, the price of generic ETV and TDF has reduced to less than10 yuan RMB per month in 11 PLADs. Indeed, data from the China Registry of Hepatitis B (CR-HepB) showed that among all CHB patients who received NA therapy, the proportion of those who received ETV and TDF had increased from 13.5% in 2003 to 79.7% in 2016 ( 42 ), and the proportions in cirrhotic paitents increased from 41.9% in 2010 to 92.8% in 2019 ( 43 ).…”
Section: Reimbursement Policy and Massive Price Reductions For Antiviralsmentioning
confidence: 99%